Global Millet Trends, Outlook, Challenges, and Opportunities - Deevi, Kumara Charyulu; Swamikannu, Nedumara; Padmanabhan, Jyosthnaa (Springer, 2024)
Millets are small-seeded coarse cereals grown mainly in Asia and Africa. Pearl millet represents about 3/4th of global millet area in the world. Africa accounts for about 64% of global millet area while Asia represents for nearly 34%. Globally, almost 3/4th of domestic supply is used for food purpose and the rest is used for feed and other uses. However, the utilization pattern is changing even in developing countries where its use in alcohol manufacture and as livestock and poultry feed is growing. The adoption of high-yielding and disease-resistant cultivars across the world (especially down mildew resistant) have increased the productivity gains consistently over time. The economic impacts of pearl millet research are well documented in literature by several studies. Except Asia region, rest of the millet growing regions in the globe are expected to supply the projected demanded of millets in their respective regions. Recurrent droughts followed by prolonged dryspells and soil moisture stress during crop growth period is the biggest challenge in both Africa and Asia. The major socio-economic challenges in case of pearl millet are follows: farmers grow it for self-sufficiency purpose rather than for market, thinly traded globally, low market demand, and lack of sufficient value addition opportunities, etc. Millet farming has a significant role in tackling the challenges of climate change, environmental degradation, and malnutrition due to its low water requirement and reduced dependency on synthetic fertilizers, etc., 2023 being the “International Year of Millets” (IYM) creating awareness among consumers about its nutritive value and other health benefits globally.